Enzymatic activity and stability of soybean oil body emulsions recovered under neutral and alkaline conditions: Impacts of thermal treatments. (January 2022) - Zhou, Xuan; Sun, Rongbo; Zhao, Jiale; Liu, Zhijing; Wang, Min; Wang, Kunyang; Jiang, Lianzhou; Hou, Juncai; Jiang, Zhanmei
Abstract: Two soybean oil body (SOB) creams were recovered from soybean at pH 7 and pH 11, respectively, and dispersed in water to obtain a natural 5% o/w emulsion. The lipoxygenase (LOX) activity and oleosin hydrolysis behavior in two SOB emulsions, as affected by different washing times and thermal treatments (50–110 °C), were investigated. The SOB emulsions recovered under neutral conditions (pH 7) were accompanied by strong enzymatic degradation. The absence of LOX and oleosin hydrolase activities was observed in SOB emulsions recovered under alkaline conditions (pH 11). The oxidative and physical stabilities of two SOB emulsions were examined at 37 °C under 15-day storage. Thermal treatment significantly enhanced the oxidative stability of two SOB emulsions due to enzymatic inactivation or altered interfacial properties. Both SOB emulsions exhibited excellent coalescence resistance after the elimination of enzymatic degradation, but their oxidative stability was different. It was due to the modification of the SOB surface by exogenous proteins that accelerated its oxidation. The results of this study might help design highly stable products based on SOB to meet the demand of people for natural products. Highlights: Recovery of SOB at neutral pH was accompanied by intense enzymatic degradation. The integrity of SOB unaffected by thermal treatment and alkaline recovery processes. SOB emulsions without enzymatic degradation exhibited good oxidative stability and resistance to coalescence. Modification of the SOB surface by exogenous proteins accelerated SOB oxidation in the absence of enzymatic activity.